If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(r + 7) = r + 1 Reorder the terms: -2(7 + r) = r + 1 (7 * -2 + r * -2) = r + 1 (-14 + -2r) = r + 1 Reorder the terms: -14 + -2r = 1 + r Solving -14 + -2r = 1 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. -14 + -2r + -1r = 1 + r + -1r Combine like terms: -2r + -1r = -3r -14 + -3r = 1 + r + -1r Combine like terms: r + -1r = 0 -14 + -3r = 1 + 0 -14 + -3r = 1 Add '14' to each side of the equation. -14 + 14 + -3r = 1 + 14 Combine like terms: -14 + 14 = 0 0 + -3r = 1 + 14 -3r = 1 + 14 Combine like terms: 1 + 14 = 15 -3r = 15 Divide each side by '-3'. r = -5 Simplifying r = -5
| A=(3Y+1)*27 | | ln(9x-1)=2 | | 17=-2x+7 | | C=0.4(t-10)+5 | | 2x+5=11-4x | | 135x^2+60x+5=0 | | 0=-2.91x-30.58 | | 3f-7=63-2f | | y=-2.91(0)-30.58 | | y=-2.91x-30.58 | | 3x+4(2x-1)=-2x+6+13x | | C=0.4t+5 | | 4-(8-7)= | | 3x+-4=-3+7 | | 3x-50=x+60 | | 8.1(0)+1.7y=9.3 | | 4(x+7)-5x+2=10 | | 8.1x+1.7(0)=9.3 | | 8.1x+1.7y=9.3 | | 2y^2+7y-49=0 | | 7n+30=-3(8-5n)+16 | | x-4y+6v= | | 3x^2+5x-17+6x+20= | | -4-10-(7-4)= | | 6(r-4)+r+30+-7R= | | -5x+21=-4 | | 49x^2-56x+7=0 | | 2a+7(3-a)=10 | | 154/165=x/100 | | (x-2)*(x^2-2*x-1)=0 | | 36=5t^2 | | 3(2x+7)-5=2(8+4x)-2x |